ANALISIS GAYA KEPEMIMPINAN NAHKODA GUNA MENUNJANG KINERJA ABK DI MV. KAIROS JAYA 8 - Mayang Defia; Achmad Ali Mashartanto; Arya Widiatmaja; Syafni Yelvi Siska; Rosnani (STKIP Subang, 2026)
The captain is the highest leader on board a ship who plays an important role in managing, directing, and supervising all operational activities of the ship. In order for the work process to run optimally, a leadership style that can effectively encourage the performance of the crew is needed. This study aims to analyze the captain's leadership style and how it supports the performance of crew members during the execution of tasks on the MV Kairos Jaya 8 ship. This study used a qualitative descriptive method with data collection techniques in the form of observations made by the researcher during the study, interviews conducted with the captain, chief officer, and crew, as well as supporting documentation obtained during the researcher's PRALA implementation on MV Kairos Jaya 8. Data analysis was carried out using Fish Bone Analysis to identify the root causes The results of research conducted during sea practice (PRALA) show that the captain's leadership style greatly affects the quality of crew work, especially in terms of communication, discipline, and completion of daily tasks. It was found that inconsistency in giving instructions, lack of a persuasive approach, and poor two-way communication can lead to delays in work and decreased crew motivation. Conversely, when the captain applies a more democratic and supportive leadership style, the crew shows a significant improvement in performance, as seen in the accuracy of task execution and increased coordination among crew members